Emerging insights into the impacts of heavy metals exposure on health, reproductive and productive performance of livestock - Afzal, Ali; Mahreen, Naima (Frontiers in Pharmacology, 2024)
Heavy metals, common environmental pollutants with widespread distribution hazards and several health problems linked to them, are distinguished from other toxic compounds by virtue of their bioaccumulation in living organisms. They pollute the food chain and threaten the health of animals. Biologically, heavy metals exhibit both beneficial and harmful effects. Certain essential heavy metals such as Co, Mn, Se, Zn, and Mg play crucial roles in vital physiological processes in trace amounts, while others like As, Pb, Hg, Cd, and Cu are widely recognized for their toxic properties. Regardless of their physiological functions, an excess intake of all heavy metals beyond the tolerance limit can lead to toxicity. Animals face exposure to heavy metals through contaminated feed and water, primarily as a result of anthropogenic environmental pollution. After ingestion heavy metals persist in the body for an extended duration and the nature of exposure dictates whether they induce acute or chronic, clinical or subclinical, or subtle toxicities. The toxic effects of metals lead to disruption of cellular homeostasis through the generation of free radicals that develop oxidative stress. In cases of acute heavy metal poisoning, characteristic clinical symptoms may arise, potentially culminating in the death of animals with corresponding necropsy findings. Chronic toxicities manifest as decline in overall body condition scoring and decrease in production potential of animals. Elevated heavy metal levels in consumable animal products raise public health concerns. Timely diagnosis, targeted antidotes, and management strategies can significantly mitigate heavy metal impact on livestock health, productive, and reproductive performance.